2006
DOI: 10.1007/s00415-006-5004-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of IVIg in autoimmune, neuroinflammatory and neurodegenerative disorders of the central nervous system: present and future prospects

Abstract: IVIg is effective in anti-GAD-positive patients with SPS. Whether it is also effective in other GAD-positive CNS disorders such as epilepsies, cerebellar degenerations or Batten's disease need to be studied in control trials. Emerging data suggest that IVIg, by suppressing proinflammatory cytokines, may exert a beneficial effect in patients with Alzheimer's disease, postpolio syndrome, chronic pain syndromes, fibrotic disorders and narcolepsy. Controlled studies are being planned or conducted to substantiate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Similarly, knowledge regarding association with disease subtypes is also important since our studies have implications for therapy of NPSLE, including targeting of IFN-α and consideration of IVIG administration. IVIG has successfully been used to treat anecdotal cases of NPSLE (42) as well as other neuroinflammatory and neurodegenerative disorders (43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, knowledge regarding association with disease subtypes is also important since our studies have implications for therapy of NPSLE, including targeting of IFN-α and consideration of IVIG administration. IVIG has successfully been used to treat anecdotal cases of NPSLE (42) as well as other neuroinflammatory and neurodegenerative disorders (43, 44). …”
Section: Discussionmentioning
confidence: 99%
“…Of note, remarkably lower levels of interferogenic activity have been observed in sera compared to CSFs of NPSLE patients. This was partially attributed to an inhibitory effect of serum IgG, providing a potential explanation for the success of intravenous immunoglobulin (IVIG) treatment in some cases of NPSLE [102] and other neurological diseases [103, 104]. In a recent study, involving 59 NPSLE patients, it was observed an association between acute flares of NP manifestations and elevated IFN α activity in the CSF [105].…”
Section: Type I Ifn and Neuropsychiatric Systemic Lupus Erythematomentioning
confidence: 99%
“…Walberer et al Alzheimer's disease, Parkinson's disease, postpolio syndrome, inclusion body myositis and amyloidosis [6] .…”
mentioning
confidence: 99%